(untitled) (Research, Society and Development, 2023)
Introduction: The use of the peripherally inserted central venous catheter (CCIP) in the Neonatal Intensive Care Unit (ICU) has been of great importance, due to the necessary procedures to be performed due to prematurity, avoiding the need for frequent venous punctures and reducing the exposure of the newborn to pain. However, its use is not free from complications. Objective: To identify the main causes for removal of the PICC catheter in the Neonatal ICU of a military hospital located in the city of Rio de Janeiro. Methods: This is a cross-sectional, descriptive and analytical study with data collection through the analysis of medical records of newborns who underwent PICC catheter insertion in the Neonatal ICU of Hospital Naval Marcílio Dias (HNMD) between June 2018 and June 2021. They were included in the study preterm newborns (PTNB) with a gestational age (GA) of less than 37 weeks and/or with a birth weight of less than 2000g. Preterm infants with PICC permanence for less than 5 days due to treatment suspension or death were excluded. Results: Detailed data analysis revealed an unexpectedly high rate of phlebitis occurrences (9.8%), even when the majority of indications for catheter removal were related to the end of treatment (78.4%). Conclusion: This scenario emphasizes the urgency of implementing solid care indicators, comprehensive checklists/bundles and standard operating procedures (SOP) to improve the standardization of care practices, aiming to improve the safety and quality of care for neonatal patients.